Ferroptosis-Related Gene BCL2L10 is Linked to Prognosis in Head and Neck Squamous Cell Carcinoma - Liu, Guancheng; Chen, Yulin; Xu, Xingnong; Zhu, Yudi; Ye, Xing; Liu, Shichao (ENT Updates, 2025)
Ferroptosis, an iron-dependent form of regulated cell death, is driven by the accumulation of lipid peroxides and shaped by mitochondrial metabolism. However, the role of BCL2L10 (B-cell lymphoma 2-like 10)—a gene previously implicated in ferroptosis—in affecting the immune microenvironment and clinical progression of head and neck squamous cell carcinoma (HNSCC) remains unclear. Using RNA-seq data from The Cancer Genome Atlas (TCGA), we compared BCL2L10 expression in HNSCC tumors and matched normal tissues and corroborated the results with immunohistochemistry images from the Human Protein Atlas (HPA). Logistic regression and Kaplan–Meier analyses were then applied to assess the relationship between BCL2L10 levels and clinical outcomes. The protein–protein interaction network centered on BCL2L10 was constructed with the STRING database, and the immunological relevance of BCL2L10 was explored through three complementary approaches: Gene Ontology (GO) annotation, gene set enrichment analysis (GSEA), and single-sample GSEA (ssGSEA). BCL2L10 mRNA levels were markedly higher in HNSCC tumors than in adjacent normal tissues. Nevertheless, univariate survival analysis revealed no significant difference in overall survival between patients with high versus low BCL2L10 expression (p > 0.05). Mechanistically, BCL2L11 emerged as a key interactor of BCL2L10, and tumors overexpressing BCL2L10 exhibited reduced infiltration by immune cells. Overall, elevated BCL2L10 expression in HNSCC is associated with an unfavorable prognosis and an immunosuppressive tumor microenvironment.